Cloning and analysis of a NBS-LRR disease resistance gene candidate PnAG1 from peanut (Arachis hypogaea L.) - Shan, Shi-hua; Zhang, Ting-ting; Li, Chun-Juan; Yang, Chen; Yan, Cai-xia; Wan, Shu-bo (Electronic Journal of Biotechnology, 2011)
Background: Based on the conserved sequences of a known NBS resistance gene, a pair of degenerate primers was designed to amplify the NBS-LRR resistance gene from peanut using PCR and RACE methods. Results: Analyzing the amino acid sequence by BLAST on NCBI, which was deduced from the 1088bp-long gene named PnAG1-2, showed that it had a certain homology with some resistance proteins, among which Arachis cardenasii resistance protein gene had the highest homology (66%). Relative quantification PCR analysis indicated that PnAG1-2 gene expresses more in J11 (an A. flavus-resistant variety) than in JH1012 (an A. flavus-susceptible variety) when the harvest time was coming. Conclusions: In this study, the NBS-LRR resistance sequence was successfully cloned from peanut and prokaryotic expression was done on the gene, which provided a foundation for cultivating anti-A. flavus peanut varieties.